Iron‐catalyzed one‐pot oxidation/Knoevenagel condensation reaction using air as an oxidant. (19th March 2019) - Huang, Lu‐Shan; Lai, Yi‐Huan; Yang, Cheng; Xu, Da‐Zhen
Abstract : A green and highly efficient iron‐catalyzed one‐pot oxidation/Knoevenagel tandem reaction for the synthesis of α, β‐unsaturated nitriles from secondary alcohols and malononitrile has been achieved. The reaction performed under mild conditions with air as an oxidant, and provided the corresponding oxidation/Knoevenagel prudocts in good to excellent yields within short times avoiding the use of noble metal catalysts and bases. Remarkably, water is the only byproduct in this methodology. The reaction could be performed on a gram scale under the standard reaction conditions. Abstract : A simple and green iron‐catalyzed one‐pot oxidation/Knoevenagel condensation the synthesis of α, β‐unsaturated nitriles from secondary alcohols has been successfully developed.